ANALISIS KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN DAN IMPLIKASINYA PADA KEPUASAN PELANGGAN PT. WILO PUMPS INDONESIA - Gulanang, Muhammad Gigih; Pramudena, Sri Marti (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2019)
Abstract. This study aims to examine and analyze the effect of product quality and brand image on purchase decision and the implication on customer satisfaction. This research was conducted at PT. Wilo Pumps Indonesia, a subsidiary company from WILO SE as a pump manufacture of Wilo brand. The research data uses primary and secondary data. Primary data is obtained through surveys with questionnaires distributes to 85 respondents who are customers of PT. Wilo Pumps Indonesia using stratified random sampling method. Secondary data is obtained from various sources such as books, journals and other published data. The analyst method uses path analysis using SPSS version 22. The results showed that product quality had a positive and significant influence on purchasing decision and customer satisfaction while the brand image had no effect on pruchasing decisions and customer satisfaction. In addition, the results of the study found that purchasing decisions have positive and significant influence on customer satisfaction.